New concept of cardiovascular disease prevention: combined treatment role - article Editorial (Кардиоваскулярная терапия и профилактика)
The Round Table Discussion «New concept of cardiovascular disease prevention: combined treatment role» was held in Moscow, July 15th 2006, with the support of «Dr Reddy’s» pharmaceutical company (India).